La restauration de My Flower Bed, de Yayoi Kusama - Camille Morineau; Patricia Dal-Prà (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Contemporary art works, and among them the installations which happen to be the origin of performances, present very specific problems to restorers. The following article relates the example of such a case, and the treatment which has been chosen. Another particularity in this case is the private sponsoring which enabled the Musée National d’Art Moderne to finance a heavy restoration of a masterpiece of the 60’s.